Preparation, characterization and antimicrobial analyses of chitosan and starch mediated copper nanoparticles - Usman, Muhammad Sani (2013)
In this study, chemical synthesis and characterization of Cu-NPs was carried out in the presence of two different stabilizers i.e. chitosan and starch polymer. The aim of this research is to individually synthesize, characterize, and test the antimicrobial activity of starch stabilized and chitosan stabilized Cu-NPs. The synthesis was carried out using aqueous medium in the presence of hydrazine as reducing agent, ascorbic acid as anti-oxidant, and sodium hydroxide as pH moderator. In determining the optimum conditions for the nanomaterials synthesis, temperature, stabilizer concentration, and reductant concentration were varied accordingly, i.e. 0.05, 0.1, 0.2 and 0.5 weight (wt)% by volume for stabilizers, 0.5, 1.0, 1.5 and 2.0 mL for hydrazine, range of 40, 80, 100 and 120°C for temperature. All the Cts/Cu-NPs and Stc/Cu-NPs synthesized were characterized using TEM, FESEM, FT-IR, UV-Vis, XRD and EDX. Following synthesis of the nanoparticles, antimicrobial analysis of the synthesized particles was investigated using different stabilizer concentrations. The UV−Vis spectroscopy results obtained for all samples showed significant surface plasmon resonance (SPR) peaks in the range of 500−600 nm, which indicated Cu-NPs formation. The molecular surface bonding of the nanoparticles and stabilizing media showed good interaction, which showed new bands at lower wave numbers (410, 600, 610 and 425), as revealed by the FT−IR spectra of all the samples. This indicates the capping of the nanoparticles by the polymers. The XRD diffractograms of samples obtained indicated high purity of the nanoparticles synthesized. No obvious peaks of CuO or Cu2O were observed. TEM analysis indicated size and size distribution of the nanoparticles differed based on the various parameters studied. FESEM micrographs of the synthesized Cu-NPs showed morphology of particles embedded within the polymer matrix. Spherical shaped nanoparticles were dominant while few hexagonal and rod-shaped were observed;depending on the conditions. Agglomeration was also noticed in samples with low stabilizer concentration. EDX spectra showed pure copper signal and carbon signal. Antimicrobial analysis conducted on the synthesized nanoparticles particles showed activity against the entire tested microorganism. Comparison between Cts/Cu-NPs and Stc/Cu-NPs showed starch as favourite among the two. With the optimization of the reaction parameters, the optimum concentrations of the reductant (0.5 mL), stabilizers (0.2 wt% for starch and 0.5 wt% for chitosan) and temperatures of 100°C for starch and 120°C for chitosan. Based on the results obtained from this experiment, the nanoparticles synthesized showed small sized nanomaterials with superb antimicrobial activity. The nanoparticles concept can serve as positive step in the fight against pathogenic microorganisms.